Mental distress and its relationship to distance education students' work and family roles. Issue 4 (1st October 2020) - Waterhouse, Philippa; Samra, Rajvinder; Lucassen, Mathijs
ABSTRACT: To date, research concerning the work-family-study interface remains limited and has focused on younger students enrolled in campus-based courses. In this study, we used self-reported data from 318 distance education final-year undergraduates to examine, first of all, the associations between students' levels of mental distress with their work and family roles. Secondly, we examined the associations between students' levels of mental distress with their perceived levels of role conflict and role facilitation. We considered conflict and facilitation both in the direction from work to studying and from family to studying. We used multinomial regression to explore relationships, controlling for age, sex, ethnicity, and educational attainment at registration. Our study revealed unpaid caring responsibilities, reported work-study conflict, and family-study conflict were associated with an increased risk of reporting higher levels of mental distress, and work-study facilitation and family-study facilitation were associated with a lower risk of reporting higher levels of mental distress.